2010
DOI: 10.5424/sjar/2010083-1266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium metabisulphite and citric acid on the shelf life of fresh cut sweet potatoes

Abstract: Minimally processed vegetables are products susceptible to chemical and biological changes, thus becoming highly perishable. During sweet potatoes (Ipomoea batatas Lam.) processing, some deteriorative reactions occur affecting quality, mainly change of color. The purpose of this research is to avoid or minimize this deterioration, so the effects of application of chemical agents to fresh cut and refrigerated stored sweet potatoes were studied, evaluating the occurrence of major organoleptic, physicochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…This indicated that chemical pretreatment was preventive against oxidation that is characterized by formation of darkened products. It has been reported that sulfites reduce o‐quinones to colorless di‐phenols thus prevent browning (Sgroppo, Vergara, & Tenev, ). The low luminosity in the control samples was indicative of possible darkening that is characteristic of enzymatic and nonenzymatic reactions that occur during heat processing Luterotti, Bicanic, and Markovi() therefore, indicating that the effect of 0.5% N.M in mitigating darkening was greater compared to that of the control and 0.5% C.C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that chemical pretreatment was preventive against oxidation that is characterized by formation of darkened products. It has been reported that sulfites reduce o‐quinones to colorless di‐phenols thus prevent browning (Sgroppo, Vergara, & Tenev, ). The low luminosity in the control samples was indicative of possible darkening that is characteristic of enzymatic and nonenzymatic reactions that occur during heat processing Luterotti, Bicanic, and Markovi() therefore, indicating that the effect of 0.5% N.M in mitigating darkening was greater compared to that of the control and 0.5% C.C.…”
Section: Resultsmentioning
confidence: 99%
“…This corresponds to maximum percentage retention of 60%, 71%, and 80% for the corresponding chemical pretreatments relative to the fresh. The higher minimization of phenolic degradation through pretreatment as compared to the control may be attributed to the ability of sodium metabisulfate and calcium chloride to retard oxidative reactions and tissue damage (Sgroppo et al., ) that may cause irreversible changes in the quality of dried produce. On the other hand, the percentage retention was 27%–59%, 42%–69%, 31%–61%, and 35%–80% for Anna F1, Kilele, Prostar F1, and Riogrande variety, respectively, depending on the drying temperatures and chemical pretreatment applied.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, polynomial equations with determination coefficients higher than 0.9 were developed to predict the sensory quality of mango fruit from textural changes for all cultivars with the exception of one (Jha et al 2011b) However, a methodology to obtain cut-off points for the physicochemical variables based on sensorial analysis has not been reported for fresh cuts. Instead, subjective analysis of the organoleptic quality changes had been used in several studies to know the shelf life of these products (Beaulieu and Lea 2003;Sothornvit and Rodsamran 2010;Sgroppo et al 2010;Chiumarelli et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Sulphite inhibits enzymatic browning by reducing o-quinones to colourless diphenol [10,11] or by reacting irreversibly with o-quinones to colourless products [12]. Sulphur dioxide and its derivatives (sulphite, bisulphite and metabisulphite) are oxidizing agents that act as preservatives and stabilizers in some products but cause allergies to some people [11].…”
Section: Introductionmentioning
confidence: 99%